عہد نبویﷺ میں خواتین کی تعلیم وتربیت (مقاصد، مراکز، اسالیب، مناہج ): Education and Moral Training in the Era of Prophet (SAW): Objectives, Centres and Methodologies. - Dr. Syed Azkia Hashmi (Seerat Studies, 2023)
The notion of social development cannot be actualized until the half of the human population (women) is provided the due rights granted to them by Islam. Acquisition of their rights, their responsibility can be performed after keeping in view the role of women and social development is the main up bringer of their children. Islam has considered seeking of knowledge is an act. The Prophet (SAW) preferred the education of women throughout His life. This article elaborates the objective, centers and methodology of women education and the establishment of these aspects.